Analysis of Raw Material Inventory Control for a Minimum Total Cost Method with EOQ (Economy Order Quantity) in PT. Citra Abadi Bosco Gresik - Sofiyanurriyanti Sofiyanurriyanti; M. Syarifuddin (International Journal of Science, Engineering, and Information Technology, 2018)
PT Citra Abadi Bosco Gresik is a company engaged in the manufacturing industry that management production on plywood wood. The company is long established, but for the past two years the company has received orders from a market that is strong enough in the production of plywood types so the demand for plywood is very optimal. The optimal supply of raw materials is one of the ways emphasis in production cost. This effort is able to minimize the cost of inventory which is the trend of raw materials inventory among companies. Raw material inventory levels are efficient enough, not too much so as to minimize expenses such as ordering costs, raw material storage costs, the frequency of raw materials purchases and the amount of raw material needs optimal, the point of reorder so that companies can obtain optimal benefits. To anticipate fluctuations in demand, seasonal demand and out of stock resulting in customers moving to other companies, so far the company is in demand to be able to serve customer demand in a timely manner, appropriate materials and exact amount of production. Smooth process in production, it is necessary a control system to get a minimum total cost. One is the Economy Order Quantity (EOQ) method. Predicting past data by predicting future forecasts is very influential and helpful in predicting future production figures by requiring existing data in the past. The results of the calculations performed on the forecast using the method of winter multiplicative model obtained from meranti raw materials of 1892.146 m3, melamine raw material of 3188.136 liters, resin raw material of 6064,477 liters, and raw materials gumtape of 1727.495 kg. Control of plywood raw material inventory according to EOQ method can be seen that the value of raw materials meranti large amount economical order 19 m3. Frequency of booking every year 99 times. Timing between ordering of meranti timber 3 days. Safety stock 51 m3. Reorder point 76.47 m3. Total cost of supplies is Rp.3,788,373,732. Melamine raw material large number of economical orders 152 liters. Frequency of booking every year 21 times. Intermediate time between melamine orders 17 days. Safety stock 96 liters. Reorder point 114.39 liters. Total inventory cost Rp.163.631.791. Raw material resin large amount of economic order amounted to 332 liters. Frequency of booking every year 18 times. Time between 20 days resin ordering. Safety stock 12 liters. Reorder point 47 liters. Total cost of inventory is Rp.93.732.802. Large gumtape raw material the order amount of economy 103 kg. Frequency of booking every year 16 times. The time between gumtape reservation 21 days. Safety stock of 0.699 kg. Reorder point 10 kg. Total cost of supplies Rp.35.853.476.